Pistas diretas planas para o tratamento de mordida cruzada posterior - Isper Garbin, Artênio José [UNESP]; Wakayama, Bruno [UNESP]; Reis dos Santos, Renata [UNESP]; Saliba Rovida, Tânia Adas [UNESP]; Saliba Garbin, Cléa Adas [UNESP] (My University, 2014)
The malocclusions are one focus of discussions in public health, due to which it is necessary to incorporate correction procedures that are inexpensive, easy to perform and which can be made in health services. Planas Direct Tracks meet such characteristics which make them advantageous for the crossbite correction. The aim of this study was to present a case in which correction of unilateral crossbite was performed with the resources available in a public clinic. This is a 6 year-old patient who presented functional unilateral crossbite in canines and posterior teeth. A cross decreased maxillary arch leading to a condition of unilateral posterior crossbite was detected. Occlusal adjustments were performed in canine and posterior teeth; however it was not enough to restore the occlusal balance. It was decided to prepare Planas Direct Tracks in canines, allowing functional balance, which prevented masticatory movement alteration during the growth phase and malocclusion correction. Controls were performed every six months to evaluate the patient's progress and whether or not new occlusal adjustments were necessary. Monitoring and treatment were conducted for 5 years, until stabilization of the permanent dentition ensuring treatment. It is concluded that Planas Direct Tracks were effective for the correction of unilateral posterior crossbite. So, it is essential to note that this procedure can be performed in public services.
Planas direct tracks for the treatment of posterior crossbite
Keywords: crossbite; malocclusion; treatment